Health-related components in plant bean seeds grown under irrigation and terminal drought stress - Herrera Hernández, María Guadalupe; Acosta Gallegos, Jorge Alberto; Salinas Pérez, Rafael A.; Bernardo Casas, Ana María; Guzmán Maldonado, Salvador Horacio (Revista Mexicana de Ciencias Agrícolas, 2018)
It reduced the knowledge about the effects of water stress on bean grain constituents. An experiment with eight bean genotypes differing genetic backgrounds of two contrasting regions (Celaya, Guanajuato and Ahome, Sinaloa) during 2007-2008. The plants were grown under irrigation and terminal drought stress. Total phenols were quantified, condensed tannins and seed oligosaccharides in raw and cooked. Independent of the factors under study, cooking certain compounds decreased (p< .01). Sinaloa harvested seed sown under water stress showed higher total phenolic content, while the irrigated harvested in Guanajuato, showed higher content of condensed tannins and oligosaccharides. For total phenolics and condensed tannins, the seed of the cultivars of race Jalisco, pink, were higher than Pinto Durango race bean and Yellow, Nueva Granada race. In oligosaccharides seed Yellow pinto cultivars showed higher seed content pink. Among the pintos, Zapata was superior to Saltillo in the total phenolic content and condensed tannins. No clear trend was observed in the oligosaccharide content between bean genotypes in response to water stress terminal. The terminal water stress showed a specific effect on total phenols, while I was watering for condensed tannins and oligosaccharides. The seed harvested in Sinaloa showed higher content of the components studied, the seed harvested in Guanajuato. The terminal drought had a specific effect of location and genotype on the contents of raw seed components.
Keywords: Phaseolus vulgaris L.; environment; genotype; irrigation; health